Effects of increasing dietary lysine on growth performance of pigs fed ractopamine HCl (paylean®) - Neill, C.R.; Hastad, C.W.; Usry, J.L.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 919 gilts (PIC L337 × C22) were used in a 21-d trial conducted in a commercial research facility to determine growth and carcass effects of ractopamine HCl (Paylean®; 6.5 g/ton) and different levels of lysine. The diets were formulated to contain 0.75, 0.85, 0.95, 1.05, 1.15, and 1.25% true ileal digestible (TID) lysine to determine the lysine requirement for pigs fed ractopamine. These TID lysine levels correspond to 0.86, 0.97, 1.08, 1.19, 1.29, and 1.40% total lysine. From d 0 to 14, pigs fed 1.05% TID lysine had the greatest improvement in ADG and F/G. In the overall (d 0 to 21) data, however, pigs fed 1.15% TID lysine had the greatest improvement in ADG and F/G. Average daily gain increased (linear, P<0.005), whereas there were no differences in ADFI (P>0.05). Feed efficiency also improved (linear, P<0.005; quadratic P<0.07). Although the ADG and F/G responses were linear, there was very little improvement observed beyond 1.15% TID lysine. Percentage lean increased (linear, P<0.03) and FFLI tended to increase (linear, P<0.07) with increasing levels of TID lysine. The lean premium increased (linear, P<0.05) and backfat tended (linear, P<0.08) to improve, but other carcass criteria were not affected. Therefore, pigs fed ractopamine required between 1.05 and 1.15% TID lysine (1.19 to 1.29% total lysine) to maximize growth performance.
Swine research, 2005 is known as Swine day, 2005
Keywords: Carcass parameters; Lysine; Paylean; Swine